Complementary effects of probiotics and stimbiotics inclusion on growth performance, protein utility, serum metabolites and behavioural observations in broiler chickens exposed to cyclic heat stress - RM. Mokonyama; U. Marume; Ghaneshree Moonsamy (Poultry Science)
The study investigated the complementary effects of probiotics and stimbiotics inclusion on growth performance, serum metabolites and behavioural responses in broiler chickens exposed to cyclic heat stress. Six hundred Cobb500 day-old-chicks were allocated to five dietary treatments: Standard broiler diet, with no inclusion of AGPs (NegControl); Standard broiler diet, with inclusion of AGPs (PosControl); Standard broiler diet + 0.01 % probiotics (Prob); Standard broiler diet + 0.01 % stimbiotics (Stim) and Standard broiler diet + 0.01 % probiotics and 0.01 % stimbiotics) (ProbStim). Each dietary treatment was replicated 8 times, with a pen holding 15 birds as the experimental unit. The experimental trial was conducted over three feeding phases: starter phase (day 1- 14), grower phase (day 15- 28) and finisher phase (day 29- 42). The birds were subjected to heat stress in the grower phase and finisher phase for 3 h (11:00- 14:00 h). Diet had no effect on ADFI in the starter, grower and finisher phase. Similarly, diet had no effect on ADG and FCR in both grower and finisher phase. The cumulative weight gain was consistently low in broiler chickens fed the Stim diet throughout the feeding phases, while those fed Prob diet had higher weights in week 2 and to 6. Dietary treatments did not affect protein consumed, protein efficiency ratio, specific growth rate and growth efficiency across all the feeding phases. Total cholesterol and triglyceride concentrations were significantly affected by diet (P < 0.05) with broiler chickens fed PosControl in non- stressed environment having the highest total cholesterol (3.90± 0.18) and triglyceride level (1.77± 0.12). With regards to behavioral response to heat stress induced discomfort, broilers fed PosControl (2.33±0.26) and Prob (2.33±0.26) exhibited increased pecking feed activity and increased tendencies of seeking cooler areas. Overall, the birds did not show signs of severe stress. In conclusion, Probiotics and Stimbiotics could be used in combination to replace of AGPs without negatively affecting productivity in broilers.